Hypothetical modality : grammaticalisation in an L2 dialect - Ziegeler, Debra (Studies in language companion series, 2000)
This book marks a new development in the field of grammaticalisation studies, in that it extends the field of grammaticalisation studies from relatively homogeneous languages to those possessing well-established and institutionalised second language varieties. In Hypothetical Modality, special reference is made to Singaporean English, a native-speaker L2 dialect of considerable importance in the South-East Asian region, and to the expression in the dialect of hypothetical modality, which appears to be indistinguishable from non-hypothetical modality in terms of the use of preterite or past for.